First use of the Adolescent Depression Rating Scale (ADRS) in the management of young people with severe acne treated with isotretinoin: a pilot study of an active monitoring of depressive disorders by dermatologists. (1st April 2022) - Hefez, L.; Micallef, J.; Revah‐Levy, A.; Falissard, B.; Jouve, E.; Dreno, B.; Chosidow, O.
Summary: Background: During isotretinoin treatment, special attention is required to detect any symptom or change in the mental health of patients. The monitoring is complex for adolescents because of confounding factors such as mood changes associated with adolescence and puberty and the higher psychosocial impairment due to the acne itself. Aim: To determine the utility of the Adolescent Depression Rating Scale (ADRS) for monitoring symptoms in adolescents before and during isotretinoin treatment in dermatology real‐life practice. Methods: This was a national, multicentre prospective study that enrolled a random sample of dermatologists treating adolescents. An algorithm including ADRS score and its changes between consecutive visits was used. At each visit, dermatologists rated their satisfaction with ADRS and its ease of use, while patients rated the acceptability of the ADRS. Results: In total, 70 dermatologists used the algorithm for 1227 visits of 283 adolescents receiving isotretinoin. Of these 70 dermatologists, 80.8% were satisfied/very satisfied with the ADRS, 82.7% considered the use of the ADRS in clinical practice to be easy/very easy and 75% considered that the ADRS enabled them to discuss more easily the risk of depression with their patients. For the patients, acceptability of the ADRS was considered good by 93.8%. Conclusions: The implementation of the ADRS could be valuable in dermatology practice, optimizing the monitoring of patients and the good use of isotretinoin. Abstract : During isotretinoin treatment, special attention is required to detect any symptom or change in mental health. Our pilot, national, multicentre, prospective study assessed the acceptability of the Adolescent Depression Rating Scale for monitoring symptoms among adolescents before and during isotretinoin treatment in dermatology real‐life practice.